The effect of the veen diagram strategy on productive thinking among middle school students in history (Texas Journal of Multidisciplinary Studies, 2025)
The aim of the current research is to find out (the effect of the veen diagram strategy on productive thinking among middle school students in history), where the researcher used the experimental method and a post-test design, and the sample size was composed of (73 students) from the fourth literary students, with a ratio of (35) and ( 38) respectively for the experimental and control groups, and a test for productive thinking was prepared. The analysis of the statistical data was all good, and the results were in the interest of the experimental group that studied according to (the veen diagram strategy). Thus, the experimental group agreed on the control group.